Philippines 2000 and the Politics of Reform - Malaluan, Nepo A. (Kasarinlan: Philippine Journal of Third World Studies, 2008)
This essay is an attempt to wade through the perceived ongoing changes in state politics. Indeed, how does one, couched in the analysis that the state is a mere appendage of comprador capitalists, react when the state starts to condemn the "oligarchy?" It discusses the Philippines 2000 as a radical project, a project of flaws, a project of uncertainties, a painful operation, etc.